Beyond survival: the lasting effects of premature birth - Morniroli, Daniela; Tiraferri, Valentina; Maiocco, Giulia; De Rose, Domenico Umberto; Cresi, Francesco; Coscia, Alessandra; Mosca, Fabio; Giannì, Maria Lorella (Frontiers in Pediatrics, 2023)
Preterm birth, defined as birth before 37 weeks of gestation, is a major public health concern. It affects about 10% of all newborns globally and is the main cause of infant death and morbidity [1]. Prematurity increases the likelihood of respiratory distress syndrome, cerebral palsy, and developmental abnormalities. Furthermore, premature newborns are at risk of acquiring chronic noncommunicable diseases later in life due to interference with organ system development during the in-utero and perinatal period. Because of the greater risk of long-term repercussions, preterm birth should be considered a chronic disorder, and gestational age and other birth histories should be included in all medical records for patients of all ages, especially when assessing the risk of multiple chronic diseases. Conventional methods for assessing preterm infant development, as well as reliable and precise growth monitoring, can lead to the early detection of growth decline and the adjustment of feeding regimens as needed. Because of its unique composition and useful components, human milk is a powerful tool for mitigating the negative outcomes associated with prematurity. It contains a variety of growth factors that promote the development of organs and systems, counteracting the negative effects of the abrupt interruption of intrauterine development and promoting better outcomes in all altered functions Despite its multiple benefits, human milk cannot totally restore the lasting damage caused by premature birth. Premature infants cannot be completely overcome by nutrition alone, and yet adequate nutritional intake and human milk feeding are critical to their health and development.